El sistema de control interno y su influencia en la gestión administrativa en el distrito de educación 12d01 Babahoyo periodo 2016-2017. - Díaz Jordán, Adriana Lisset (2019)
This research paper called “THE INTERNAL CONTROL SYSTEM AND ITS INFLUENCE IN ADMINISTRATIVE MANAGEMENT IN THE EDUCATION DISTRICT 12D01 BABAHOYO PERIOD 2016-2017” establishes as a general objective to evaluate the internal control system and its influence on administrative management. The specific objectives were aimed at examining the planning and control system of the institution, analyzing the control system it employs and defining the level of effectiveness and efficiency of the district's internal control system. The methodology to be implemented in the research is inductive, descriptive and analytical, developed in the administrative area of the District Department of Education and the various units that comprise it. The instruments to be used in the collection of information are surveys and interviews directed to the officials and directors of the institution allowing to verify the various existing problems, which determines the need to implement an internal control system applied to the administrative management of the district of Education 12D01 that serves to guide the administration of the entity to optimize its management, obtain better results and meet the institutional objectives. Keywords: Internal control, Administrative management, Administration processes, Education District, Evaluation.